Doctrine of organization agreement on collective security - Bardžić Žikica; Đurić Dragomir (Oditor, 2016)
Organization of the Collective Security Treaty (CSTO) is a security integration in the Eurasian region. In the framework of the CSTO after a long time and many changes and corrections, made functional and clear organizational structure. This process was from the original DKB as almost a political organization, through DKB war and especially the CSTO as a complete military-political integration on post-Soviet space. Today, the CSTO has a completely clear and manageable structure, starting from the highest authority and the Collective Security Council, through the Council of Foreign Ministers, the Council of the Ministry of Defense, the Secretary of the Security Council Committee CSTO and other organs. All decisions, other than procedural, are taken by consensus. The biggest disadvantage of the functionality of the CSTO, it can be pointed out the lack of authority for the settlement of disputes between States. Also, as a deficiency can be treated and that so far some issues related to the mechanism of adoption and the legal empowerment of the decisions taken by the authorities of the CSTO, remained unresolved.